Antimicrobial and antioxidant activities of Saccharomyces cerevisiae IFST062013, a potential probiotic. Issue 1 (December 2017) - Fakruddin, Md.; Hossain, Md.; Ahmed, Monzur
Abstract Background Probiotic yeast has become a field of interest to scientists in recent years. Methods Conventional cultural method was employed to isolate and identify yeast and standard methods were used to determine different probiotic attributes, antimicrobial and antioxidant properties. Results This study reports potential probiotic properties of a strain ofS. cerevisiae IFST 062013 isolated from fruit. The isolate is tolerant to a wide range of temperature and pH, high concentration of bile salt and NaCl, gastric juice, intestinal environment, α-amylase, trypsin and lysozyme. It can produce organic acid and showed resistance against tetracycline, ampicillin, gentamycin, penicillin, polymixin B and nalidixic acid. It can assimilate cholesterol, can produce killer toxin, vitamin B12, glutathione, siderophore and strong biofilm. It showed moderate auto-aggregation ability and cell surface hydrophobicity. The isolate can produce enzymes such as amylase, protease, lipase, cellulose, but unable to produce galactosidase. The isolate can't produce gelatinase and DNase. The isolate showed moderate anti-microbial activity against bacteria and fungi and cell lysate showed better antimicrobial activity than whole cell and culture supernatant. Again, the isolate showed better anti-bacterial activity against gram negative bacteria than gram positive. The isolate showed strong antioxidant activity, reducing power, nitric oxide and hydroxyl radical scavenging activity, significant brine shrimp cytotoxicity and acute toxicity and metal ion chelating activity. The isolate did not induce any detectable change in general health of mice upon oral toxicity testing and found to be safe in mouse model. The isolate improve lymphocyte proliferation and cytokine production in treated mice. Conclusions Such isolate could be potential as probiotic to be used therapeutically.